Penerapan Pajak Karbon dalam Mewujudkan Sustainability Development Goals Serta Dampaknya Terhadap Penerimaan Pajak di Indonesia - Meila, Kaca Dian; Dianty, Astari; Veronica, Lydia (Owner : Riset dan Jurnal Akuntansi, 2024)
Climate change is caused by the burning of fossil fuels that produce greenhouse gas emissions that can raise temperatures globally. The government is trying to control climate change, one of which is by setting targets for reducing greenhouse gas emissions and implementation a carbon tax. The implementation of carbon tax is change industrial behavior to switch green economy activites that are low in carbon emissions. The purpose of this research is to forecast the impact of carbon tax on potential state revenue to reduce the amount of carbon emissions in Indonesia to support the achievement of Sustanability Development Goals (SDGs).  The method of the research used is qualitative method with content analysis approach using corbon emission data from Statistical Review Energy 2023 and scoping review approach from national and international literature such as working papers, scientific articles, etc obtained based on keyword for from search engine. Based on the scoping review step, 5 articles were obtained that can detail represented about the implementation of carbon tax can be reduce carbon emission to realize the Sustainability Development Goals (SDGs) in the Asia Pacific. The energy sector was chosen because the consumption has increased, energy sector is the largest contributed carbon dioxide consumption globally was compared to other sectors due to increased combustion activities of carbo containing compounds. Based on the result, implementation of carbon tax have applied by the government could be provide potential state revenue from the energy sector worth IDR23.280 trilion in 2025. The potential tax revenue generated from carbon tax ca be used to the impacts of climate change to support the achievement of Sustainability Development Goals (SDGs). The implementation of carbon tax is expected to change industry behaviour to green economic activities that are low in carbon emission leading to the achievement of the SDGs